関節突起部に生じた周辺性骨腫の1例 - 増田, 智丈; 古郷, 幹彦; 沢井, 奈津子; 原田, 計眞; 太田, 之博; 相川, 友直 (日本口腔外科学会雑誌, 2009)
Osteoma is a benign tumor consisting of mature bone tissue. A solitary osteoma is classified as peripheral when it arises from the periosteum, central when it arises from the endosteum, and extraskeletal when it arises in soft tissue. Solitary osteomas occur mainly in the craniofacial bones. Peripheral osteomas arising in the condylar process of the mandible are rare. Here, we report a case of peripheral osteoma of the condylar process in a 62-year-old woman who complained of a cosmetic disturbance. The osteoma, 48 X 43 X 37 mm in a diameter, was surgically excised by a submandibular approach. The histopathological diagnosis was a compact osteoma. The patient remains free of recurrence after 1 year.